The Effect of Doping Concentration in the Work Electrodes of Graphene-MnxOy and Test on Glucose by Cyclic Voltametry - L Agusu; T. Azis; Imran; Fitrianti; A. T. Nurwahida; S. Misudo; Alimin (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2024)
A study was conducted to investigate the impact of concentration on the graphene-manganese oxide (EPG/MnxOy) working electrode for glucose analysis using the cyclic voltammetry method. To characterize the electrode material, SEM-EDX, FTIR, and XRD analyses were performed. The results revealed that the graphene surface contained aggregates in the form of small particles attached to the graphene. Various absorption bands corresponding to aliphatic -O-H, -C-H, -C=C aromatic, -C=O, -C=C, -C-O, and Mn-O groups were identified in the graphene and graphene/MnxOy materials. Crystal patterns of manganese oxide were also identified at angles 2q = 30.57o and 44.39o, representing the Mn3O4 crystal pattern, at the angle 2q=34.12o denoting the MnO2 crystal pattern, and at angles 2q= 39.85o, 57.85o, and 68.94o representing the MnO crystal patterns. The optimal electrode composition was found to be graphene:MnxOy 0.8:0.5, as indicated by an anodic peak current (Ipa) of 122 µA at a potential of -0.11 V. The most effective supporting electrolyte was determined to be NaNO3, with an anodic peak current (Ipa) of 26.4 µA at a potential of -0.13 V. The detection limit for glucose was 4.45×10-3 M. The repeatability test of EPG/MnxOy yielded a result of 1.77%.